Broaching 'themes too large for adult fiction': the child narrator in NoViolet Bulawayo's We Need New Names. Issue 1 (2nd January 2016) - Wilkinson, Robyn
Abstract : This article explores the use of a child narrator in NoViolet Bulawayo's We Need New Names (2013. New York: Back Bay Books). The novel is told through the voice of a ten-year-old girl named Darling, who provides an account of her life in Zimbabwe in the first part of the novel, and of her experiences as an immigrant in America in the second part. Darling is old enough to have some understanding of the world she lives in, but is not yet a fully socialized adult, and Bulawayo makes deft use of her liminality in order to provide an innovative critique of a large number of issues facing Zimbabwe at present. This article focuses predominantly on her presentation of the corruption of the leaders of religious and political institutions in Zimbabwe, and argues that through the overly-confident and naively honest register of a child, Bulawayo is able to transcend public opinion and social correctness in order to point out the shortcomings of these leaders, and to tentatively hope that by bringing these realities to light, positive change in her home country may be a possibility.